An electrochemical sensor with a copper oxide/gold nanoparticle-modified electrode for the simultaneous detection of the potential diabetic biomarkers methylglyoxal and its detoxification enzyme glyoxalase. (11th October 2019) - Rajpurohit, Anuja S.; Punde, Ninad S.; Srivastava, Ashwini K.
Abstract : Highly sensitive electro-oxidation of the MGO and GLO biomarkers at the CuO/Au/GCE sensor employing the AdSDPV method. Abstract : Methylglyoxal (MGO) is a major pioneer material for the formation of advanced glycation end products (AGEs) during the glycation reaction, whereas glyoxalase (GLO) is an enzyme that detoxifies excess MGO accumulated in the body. In this study, an electrochemical sensor for the simultaneous detection of MGO and GLO as potential diabetic biomarkers was developed using a copper oxide/gold nanoparticle (CuO/Au)-modified glassy carbon electrode (GCE) in a neutral pH medium using 0.1 M phosphate buffer, and adsorptive stripping differential pulse voltammetry (AdSDPV) was employed to obtain the results. The morphology and structural aspects of the CuO/Au nanocomposite were examined by various material characterization techniques, which revealed that Au nanoparticles were evenly scattered on CuO nanoplates. MGO and GLO exhibited two well-defined voltammetric signals at the CuO/Au/GCE, and this modifier displayed potent electrocatalytic activity, resulting in significant enhancement of their peak heights. Under optimized experimental conditions, the wide dynamic linear calibration ranges of 0.008–55 μM and 0.006–50 μM with the detection limits of 2.35 nM and 1.75 nM were achieved in the simultaneous determination of MGO and GLO, respectively. The developed protocol was applied to the human plasma and urine samples of healthy individuals and diabetic patients for the specific and accurate determination of MGO levels.